2016
DOI: 10.18632/oncotarget.12803
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of glioma cells to nutrient-deprived microenvironment can be enhanced by CD133-mediated autophagy

Abstract: CD133 is a pentaspan transmembrane protein that can serve as a biomarker for cancer stem cells, although its biochemical mechanism remains unclear. Here we report that CD133 expression enhances glioma cell tolerance of a nutrient-deprived microenvironment. Under starvation conditions, CD133-positive cells exhibited higher survival and decreased levels of apoptosis. These changes were dependent on activation of autophagy-associated gene signaling and were impaired by the autophagic inhibitor chloroquine. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…Notably, CD133 has been indicated to improve the resistance of glioma cells to a nutrient-deprived microenvironment by participating in autophagosome biogenesis ( 33 ). Meanwhile, Chen et al ( 24 ) found that CD133 is involved in cell survival through regulation of autophagy and glucose uptake in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, CD133 has been indicated to improve the resistance of glioma cells to a nutrient-deprived microenvironment by participating in autophagosome biogenesis ( 33 ). Meanwhile, Chen et al ( 24 ) found that CD133 is involved in cell survival through regulation of autophagy and glucose uptake in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…A report has described that activation of autophagy is critical for cancer cellular survival under nutrient starvation (39). Another report also demonstrates that CD133-positive glioma cells exhibit higher survival under starvation conditions, which depends on induction of autophagy (40). Furthermore, autophagy induced by amino acid starvation is accelerated in the multidrug-resistant cells when compared to parental cells, resulting in enhanced cell survival capacity (41).…”
Section: Discussionmentioning
confidence: 99%
“…During tumorigenesis, decreased mitophagy may lead to the persistence of damaged mitochondria in cells, which may result in higher levels of tumor-promoting ROS or other mitochondrial signals (25). By contrast, established tumors may require mitophagy for stress adaptation and survival (25,27,28). Despite the multitude of mechanisms that have been proposed to explain the mitochondrial dynamics in tumor cells, the effects of inflammation on this cellular event in glioma remain uncharacterized.…”
Section: Glioma Cells Are Resistant To Inflammation-induced Alteratiomentioning
confidence: 99%